Hubungan antara Pola Asuh Keluarga dengan Kejadian Balita Stunting pada Keluarga Miskin di Palembang - Febriani Dwi Bella; Nur Alam Fajar; M Misnaniarti (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: Stunting is a result of a malnutrition state that accumulates for an extended time and is a threat to the future of Indonesian children. The incidence of toddler’s stunting is indirectly related to the role of parenting in the family, namely feeding, nurturing, hygiene and getting health services. The aim of the study was to analyze the correlation of parenting to the incidence of toddler’s stunting on poor families in Palembang.Methods: This research was an observational study which using a quantitative approach with a Cross Sectional Study design on March 2019. Data samples of 100 mothers who had children aged 24-59 months from poor families in Palembang were chosen by proportional random sampling.Result: The results showed that the proportion of toddler’s stunting in poor families in Palembang was 29%. The results of bivariate analysis showed that there was a relationship between feeding habits (p = 0,000); parenting habits (p = 0.001); hygiene habits (p = 0.021); and the habit of getting health services (p = 0,000) with the incidence of stunting for toddlers.Conclusion : Normal height (not stunting) toddlers have parenting habits such as feeding habits, nurturing habits, hygiene habits and the habit of getting health services better than stunting toddlers in the same economic backgrounds family.